Penggunaan Media Kartu Gambar Untuk Mengatasi Hambatan Kemampuan Artikulasi Huruf Konsonan Pada Anak Usia 5-6 Tahun - Putri Sri Suryadi , Delika; Azhar Yanmin, Alfian; Hendri Mulyana, Edi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to examine the effectiveness of using picture card media in overcoming articulation difficulties of consonant sounds in children aged 5–6 years. Articulation problems, such as inaccurate pronunciation of sounds like /d/, /g/, /p/, /f/, and /r/, can hinder children's language and communication development. The research employed an experimental method using a Single Subject Research (SSR) approach with an A-B-A design, consisting of three phases: baseline-1 (A1), intervention (B), and baseline-2 (A2). The subject of the study was a single child experiencing articulation difficulties with consonant sounds. Data were collected through structured observation using an articulation assessment instrument and analyzed descriptively with visual graph representation. The results showed a significant improvement in the child’s articulation ability after the intervention using picture card media. In the A1 phase, the average articulation percentage was 34.15%, which increased to 78.18% during the intervention phase (B), and remained at 76.33% in the A2 phase. This improvement indicates that picture card media can strengthen children's visual-verbal associations with letter sounds, enhance concentration, and motivate them to pronounce consonants more accurately. This study recommends the use of picture card media as a fun, structured, and effective learning alternative for teachers and parents in supporting early childhood language development, particularly in addressing consonant articulation difficulties